Frequency of FLT3/ITD Mutation in Patients with Acute Myeloid Leukaemia presenting at Combined Military Hospital, Rawalpindi - Babar, Anil; Ahmad, Riaz; Piracha, Muhammad Nadeem; Amin, Zulfiqar Ali; Raza, Ahmed; Zargham, Anum (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the frequency of FLT3/ITD mutation in patients of Acute myeloid leukaemia presenting at Combined Military Hospital, Rawalpindi Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: Oncology Department, Combined Military Hospital, Rawalpindi Pakistan, from Jan to Jun 2020.Methodology: A sample of 46 patients with acute myeloid leukaemia was included using a non-probability, consecutive sampling technique. Genetic testing was done on all blood samples to identify FLT3-ITD mutation.Results: Out of 46, 10(21.7%) were females and 36(78.3%) were males. The FLT3/ITD mutation frequency in our study sample was 10(21.7%), with all in de-novo AML patients and none in secondary AML. White cell count (55x109), bone marrow blasts (85%) and peripheral smear blasts (75%) were high in the FLT3-ITD mutated group in comparison to the non-mutated group.Conclusion: Timely detection of FLT3/ITD mutation and an amplification of induction therapy would benefit this group of patients.